Regulatory T cells and immunoglobulin E: A new therapeutic link for autoimmunity?. Issue 11 (27th July 2022) - Palomares, Oscar; Elewaut, Dirk; Irving, Peter M.; Jaumont, Xavier; Tassinari, Paolo
Abstract: Autoimmune diseases have a prevalence of approximately 7 to 9% and are classified as either organ‐specific diseases, including type I diabetes, multiple sclerosis, inflammatory bowel disease and myasthenia gravis, or systemic diseases, including systemic lupus erythematosus, rheumatoid arthritis and Sjögren's syndrome. While many advancements have been made in understanding of the mechanisms of autoimmune disease, including the nature of self‐tolerance and its breakdown, there remain unmet needs in terms of effective and highly targeted treatments. T regulatory cells (Tregs) are key mediators of peripheral tolerance and are implicated in many autoimmune diseases, either as a result of reduced numbers or altered function. Tregs may be broadly divided into those generated in the thymus (tTregs) and those generated in the periphery (pTregs). Tregs target many different immune cell subsets and tissues to suppress excessive inflammation and to support tissue repair and homeostasis: there is a fine balance between Treg cell stability and the plasticity that is required to adjust Tregs' regulatory purposes to particular immune responses. The central role of immunoglobulin E (IgE) in allergic disease is well recognized, and it is becoming increasingly apparent that this immunoglobulin also has a wider role encompassing other diseases including autoimmune disease. Anti‐IgE treatment restores the capacity of plasmacytoid dendritic cells (pDCs) impaired by IgE‐ high‐affinity IgE receptor (FcεR1) cross‐linking to induce Tregs in vitro in atopic patients. The finding that anti‐IgE therapy restores Treg cell homeostasis, and that this mechanism is associated with clinical improvement in asthma and chronic spontaneous urticaria suggests that anti‐IgE therapy may also have a potential role in the treatment of autoimmune diseases in which Tregs are involved.